1972
DOI: 10.1113/jphysiol.1972.sp009835
|View full text |Cite
|
Sign up to set email alerts
|

The release of prostaglandins and progestin into the utero‐ovarian venous blood of guinea‐pigs during the oestrous cycle and following oestrogen treatment

Abstract: SUMMARY1. Blood was collected from the utero-ovarian vein of guinea-pigs on days 3, 9, 10, 11, 12, 13, 14 and 15 of the oestrous cycle, and from animals injected with oestrogen over days 4-6 and used on day 7. The content of prostaglandin F2, and E2 was determined by bio-assay and gas chromatography-mass spectrometry, and ofprogestin by competitive protein binding assay.2. The concentration of prostaglandin F2 on day 3 was 14 1 ngfml.; it fell below detectable limits on day 7, but after day 11 the concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
71
0

Year Published

1975
1975
1994
1994

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(78 citation statements)
references
References 23 publications
7
71
0
Order By: Relevance
“…This increase in oestradiol output from the ovary precedes an increase in PGF2. output from the uterus by 24 h (Blatchley et al, 1972;Earthy et al, 1975;Antonini et al, 1976). Oestradiol acting on a progesterone-primed uterus appears to be the physiological stimulus for increased PGF2.…”
Section: Discussionmentioning
confidence: 99%
“…This increase in oestradiol output from the ovary precedes an increase in PGF2. output from the uterus by 24 h (Blatchley et al, 1972;Earthy et al, 1975;Antonini et al, 1976). Oestradiol acting on a progesterone-primed uterus appears to be the physiological stimulus for increased PGF2.…”
Section: Discussionmentioning
confidence: 99%
“…However, the measurement of PGF-2\g=a\levels in the utero-ovarian venous plasma of cyclic guinea-pigs (Blatchley, Donovan, Horton & Poyser, 1972) revealed that, even though the concentration was low, PGF-2\g=a\was present throughout the oestrous cycle and that there was asynchrony in luteal regression (Days 12\p=n-\16: Rowlands, 1956) and the peak of PGF-2\g=a\secretion (Day 15: Blatchley et al, 1972). During experiments to study the effects ofPGF-2\g=a\on the different tissue components of the ovary, it was found that the CL responded to the luteolytic action of PGF-2\g=a\only at certain times.…”
mentioning
confidence: 99%
“…Bland & Donovan (1968 have shown that injections of oestradiol benzoate on days 3-11 of the oestrous cycle, or a single injection on day 3 led to regression of the corpora lutea of guinea-pigs, an effect abolished by hysterectomy. Oestradiol benzoate injections early in the cycle also gave rise to increased prostaglandin F2a levels in utero-ovarian venous blood (Blatchley, Donovan, Poyser, Horton, Thompson & Los, 1971;Blatchley et al, 1972) though not in hysterectomized animals, indicating that the prostaglandin F2.…”
Section: Discussionmentioning
confidence: 99%
“…In the guinea-pig, the increase in oestradiol secretion from the ovary towards the end of the oestrous cycle (Joshi et al, 1973) may be the stimulus for increased prostaglandin F1 production and release from the uterus at this time (Poyser, 1972;Blatchley et al, 1972). Bland & Donovan (1968 have shown that injections of oestradiol benzoate on days 3-11 of the oestrous cycle, or a single injection on day 3 led to regression of the corpora lutea of guinea-pigs, an effect abolished by hysterectomy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation